2020
DOI: 10.3390/children7100181
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study on the Echo-Assisted Intersphincteric Autologous Microfragmented Adipose Tissue Injection to Control Fecal Incontinence in Children Operated for Anorectal Malformations

Abstract: Aim of the study: To assess the efficacy of a novel technique (echo-assisted intersphincteric autologous microfragmented adipose tissue injection, also called “anal-lipofilling”) in the management of non-responsive fecal incontinence in children born with anorectal malformations (ARMs). Methods: Following ethical committee approval (CHPED-MAR-18-02), anal-lipofilling was proposed to patients with fecal incontinence not responsive to medications or bowel management (bowel enema and/or transanal irrigation autom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Previous studies in adults [ 7 , 8 , 9 ] and our first study in a pediatric population [ 10 ] showed that, when used to treat fecal incontinence, the injected fat, in addition to its regenerative potential, acts as a bulky agent increasing the resting pressure, as verified with anorectal manometry, and thickens the anal sphincter, as documented by anal endo-sonography.…”
Section: Introductionmentioning
confidence: 58%
“…Previous studies in adults [ 7 , 8 , 9 ] and our first study in a pediatric population [ 10 ] showed that, when used to treat fecal incontinence, the injected fat, in addition to its regenerative potential, acts as a bulky agent increasing the resting pressure, as verified with anorectal manometry, and thickens the anal sphincter, as documented by anal endo-sonography.…”
Section: Introductionmentioning
confidence: 58%
“…In another study, Parente et al performed an EUS-assisted autologous intersphincteric injection of autologous microfragmented adipose tissue in four patients with FI following surgery for anorectal malformation. A significant improvement in bowel function FI scores were found ( 41 ). Meanwhile, the EUS performance needs a specific rectal 360° probe and cooperation between doctors and patients.…”
Section: Diagnosis Of Fi In Children and Adolescentsmentioning
confidence: 99%
“…SRS is generally recommended for sphincter defects, but not for neurologic incontinence. The injection of bulking agents around the anal canal can effectively reduce the frequency of involuntary FI and relieve symptoms, and can therefore be used in the treatment of sphincter-associated FI ( 41 , 81 , 82 ). Although increasing evidence shows the potential of SRS in FI, a few studies were performed in children.…”
Section: Management Of Fi In Children and Adolescentsmentioning
confidence: 99%
“…Several evidences report a significant positive clinical outcome such us in plastic surgery in the treatment of ulcers, burns, scars, soft tissue augmentation [ 5 , 7 9 ]. The application of AT-MSC was not confined to plastic surgery but was also extended to cardiac, rheumatoid, gastro-intestinal and musco-skeletal fields, etc [ 10 12 ]. For this reason, different enzymatic and mechanical procedures have been established for processing AT to isolate cells that can be locally implanted [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%